Capacity building for SMEs: realizing the training gap amongst SMEs in Malaysia - Abdullah, Moha Asri; Abdul Razak, Dzuljastri; Azam, Md Siddique; ., Winarsih; Akbar, Taufik (UMY Press, 2020)
Small and medium enterprises (SMEs) contribute a significant portion to the economic pie both in the developed and developing countries. The devel-opment and growth of SMEs in Malaysia has significant impact on social development, boosting productivity and increasing employment. Training is one of the issues and challenges faced by SMEs studied by previous research-ers. Studies also find training as one of the potential tools for capacity build-ing of SMEs. Hence, to ensure the sustainability of the SMEs, an understand-ing of their training status is worth studying. This chapter identifies the back-ground of SMEs in Malaysia, provides an indicator on the training require-ments and the type of training received by SMEs in different fields. The survey was conducted using structured questionnaire that involved questions re-garding the type of training received and needed by SMEs in different fields of business. A total of 344 respondents were surveyed and then analyzed using descriptive statistics as well as SPSS software. More than half of the respondents did not have any prior business experience. Training gap was measured by looking into the differences between the training received and the training requirements of SMEs. From the analysis and observation, a sig-nificant training gap was revealed among the SMEs in terms of what they have received and what they require currently as well as in the future. This difference was further confirmed by ‘t-test’. A significant correlation was found between the training received and the training requirements of SMEs. Higher training requirements were associated with higher training received. The majority of the respondents required training in all the mentioned fields in both current and future times. It was also found that there was an increase in the training requirements compared to what they received. This finding sup-ports the training gap and correlation realized in this chapter.